The Model of the Extraction Process of Rare Metals Under Condition of Filtration Combustion Wave - Salgansky, Eugene A.; Lutsenko, Nickolay A.; Toledo, Mario (Frontiers in Chemistry, 2020)
To study the mass transfer of metal compounds, a model of filtration combustion of metal-containing combustible mixtures is developed. Using cadmium-containing mixture as an example, the main characteristics of filtration combustion are determined when the gas pressure at the reactor inlet is constant. It is shown that under the conditions of a filtration combustion wave, a metal can evaporate into the gas phase and be transferred with gas through the reactor. Due to the evaporation and condensation of cadmium, it is transported and accumulated before the combustion front. The possibility of controlling the mass transfer of metal compounds under the conditions of a filtration combustion wave with the aim of concentrating them is shown. It is revealed that a 4-fold increase in the pressure difference at the open boundaries of the reactor can lead to a decrease in the maximum metal concentration by about 1.5 times. An increase in the concentration of metals due to mass transfer will subsequently make it economically feasible to extract them by traditional methods.